Materiais didáticos para classes de educação de jovens e adultos na visão de professoras - Azevedo, Benedita Aparecida de (2007)
This research aims to investigate the view that teachers from classes of Adult and Youth Education (EJA) from 5th to 8th grades from public state schools of Vale do Ribeira-SP have about the didactic materials used in classroom. The investigation work has the following research questions What do the teachers say about the use of the Collection Ensinar e Aprender (Teach and Learn) in classroom? What difficulties do they notice in relation to the use of that material? Which other materials have been used by those teachers? as well as the hypothesis that the material proposed and received by the teachers of EJA classes from 5th to 8th grades in the state of São Paulo (Collection Teach and Learn) has not been frequently used, once the students reach the EJA classes from 5th to 8th grades without the necessary fluency in reading and writing, compelling the teachers to use other materials. The data, collected by means of analysis of documents and interviews with 05 teachers from those classes, were organized in synthesis charts and analyzed taking into consideration the theoretical reference offered by authors who study the school in its relationship with the social structure and the culture (Pérez Gómez and Gimeno Sacristán). This dissertation is structured in order to present what the analyzed documents indicate and propose; what the analytical studies about those documents bring; what the studies on pedagogic and didactic practices for Adult and Youth Education bring; and what the investigated teachers say about their work and those materials. The results emphasize that the teachers ignore the existence of the Curricular Proposal for the 2nd segment of the Adult and Youth Education and also ignore specific materials to support their work, the reason why they are compelled to accomplish adaptations of didactic materials destined to regular classes of Primary School